Multi-objective optimisation and analysis of fused deposition modelling parameters: best infill patterns. (11th July 2022) - Patil, Pooja; Singh, Dharmendra; Raykar, Sunil Jaysing; Bhamu, Jaiprakash
Components manufactured with additive manufacturing process are always exceptional with respect to their quality in terms of shape and size. Fused deposition modelling (FDM) is one the additive manufacturing process used to manufacture high quality polymer components and prototypes. Quality of parts manufactured by FDM depends on many of its process parameters like infill percentage (infill %), layer thickness, bee temperature, speed, and infill patterns. This paper presents a multi-objective optimisation paradigm based on VIKOR-AHP for selection of best printing parameters for FDM. Layer thickness of 0.3 mm, 80 mm/s of printing speed, 50% of infill % with zig-zag pattern gives the best results in terms of FDM performance. With these settings printing times is 22 min with consumed filament length and weight are 2.25 m and 6.72 gms respectively.